Nucleotide variations of Streptococcus pneumoniae hyaluronate lyase (spnhyl) gene in clinical isolates - Ahmad Yusof @ Hanafi, Hanani; Masri, Siti Norbaya; Mohd Desa, Mohd Nasir; Osman, Malina; Jamal, Farida (2012)
Streptococcus pneumoniae is an important cause of human infections, particularly pneumonia, acute otitis media and meningitis. Hyaluronate lyase, an enzyme secreted by Streptococcus pneumoniae facilitates bacterial invasion by degradation of host connective tissue. This study was conducted to characterize the nucleotide sequence of hyaluronate lyase gene among clinical isolates of Streptococcus pneumoniae. Twenty isolates were selected comprising 13 from blood, 3 from sputum, 2 from pus and one each from cerebrospinal fluid and pleural fluid. ATCC 49169 strain was included as the positive control. DNA was extracted from all samples and PCR amplification was done using 5 sets of primers prior to sequencing the whole gene. DNA sequence analysis was done with BioEdit, NCBI Blast tools and MEGA4 software by using Streptococcus pneumoniae TIGR4 as the reference sequence. A total of 100 nucleotide variants were found among the strains which comprised 98 single nucleotide substitutions, 1 deletion and 1 insertion of triplet bases. From this result it was predicted that 53 variants could change the amino acid residue. Part of the changes involved 15 residues of both α- and β-domains, and 1 residue in the linker. Two nucleotide variations could cause earlier stop codon. Although high numbers of nucleotide variants were present, biological function of hyaluronate lyase was not likely to be affected as no catalytic active site was involved. The nucleotide variants were scattered in all strains, and did not appear to be related to the serotype or clinical source of the strain. Further studies are required to elaborate the significance of these findings.